Agricultural production mode transformation and production efficiency: A labor division and cooperation lens. Issue 1 (4th February 2019) - Liu, Zimin; Yang, Dan; Wen, Tao
Abstract : Purpose: The purpose of this paper is to analyze the impact of farmers' agricultural production mode transformation, from the perspective of agricultural division of labor and cooperation, on their agricultural production efficiency including technical efficiency, pure technical efficiency and scale efficiency. Design/methodology/approach: This paper analyzes the impact of the agricultural production mode's transformation on farmers' agricultural production efficiency, based on the classical theory of division of labor and specialization, transaction costs and cooperation. It uses 2013 survey data from 396 farms in 15 Chinese provinces to explore the contributing factors of agricultural production efficiency using a double selection model (DSM), which can correct the endogenous selection bias in farmers' decisions. Findings: Farmers that participate in agricultural division of labor and cooperation means transform their agricultural production from a traditional self-sufficient mode to one that is specialized and intensive. Agricultural division of labor measured by farmers' participation in an agricultural division of labor in the production stages, or in agricultural products, and agricultural cooperation measured by farmers' participation in farmers' cooperatives significantly and positively influence their agricultural production efficiency after correcting farmers' endogenous selection bias. Originality/value: This paper proposes a unified framework to analyze the impact of farmers' agricultural production mode transformation on their production efficiency. Further, it builds a DSM for an empirical analysis to avoid the endogenous biases in farmers' self-selection behavior. This paper also provides ways for policy makers to improve farmers' agricultural production efficiency from the modern agricultural production perspective.